Corporate social responsibility, earnings management and industry type : does CSR reinforce entrenchment strategy? - Nor Atikah Shafai; Azlan Amran; Yuvaraj Ganesan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Managers could opportunistically misuse corporate social responsibility (CSR) to obfuscate earnings management (EM) by reporting more CSR activities that eventually accomplished stakeholders’ advocacy as their demands on CSR are satisfied. Likewise, sensitive industries have a higher commitment to CSR to appease their stakeholders’ adverse reactions to the nature of their business. This study examines the relationship between EM and sensitive industries on CSR (proxied by the quality of CSR disclosure) and the moderating role of sensitive industries in the relationship between EM and CSR. Employing multiple regression analysis on Malaysian public listed companies for the year 2016, this study finds an insignificant association between EM and CSR, a positive association between sensitive industries companies and CSR and sensitive industries moderate the relationship between EM and CSR. This study offers practical implications for companies to strengthen their corporate governance mechanisms and for investors to cautiously evaluate the companies’ ethics.